A new genus for a new species of Podoscirtini from southeast Tibet (Orthoptera: Gryllidae; Podoscirtinae; Podoscirtini) - He, Zhuqing; Gorochov, Andrej V. (Zootaxa, 2015)
Most of the Chinese species of the tribe Podoscirtini are distributed in southern areas of China, especially in Yunnan Province and Hainan Island (Eades et al. 2015). Motuo County is located in southeast Tibet. In this area, altitude decreases from north to south sharply. The climate in Motuo is wet and warm, which makes the animals and plants are very different from those elsewhere in Tibet (Fig. 1, A). In 2014, two representatives of Podoscirtini were found in Motuo. One of them is Valiatrella bimaculata (Chopard, 1928) (Fig. 1, B). Another representative is the new species described in this paper. It belongs to a new genus strongly different from all the other genera of this tribe recently reviewed by Gorochov (2002–2006, 2010). Type material of this species is deposited at the Biological History Museum of East China Normal University (ECNU) and Shanghai Entomology Museum (SEM).